Multiple-Criteria Decision Making - Goran Ćirović; Dragan Pamučar (MDPI, 2022)
Decision-making on real-world problems, including individual process decisions, requires an appropriate and reliable decision support system. Fuzzy set theory, rough set theory, and neutrosophic set theory, which are MCDM techniques, are useful for modeling complex decision-making problems with imprecise, ambiguous, or vague data.This Special Issue, "Multiple Criteria Decision Making", aims to incorporate recent developments in the area of the multi-criteria decision-making field. Topics include, but are not limited to:- MCDM optimization in engineering;- Environmental sustainability in engineering processes;- Multi-criteria production and logistics process planning;- New trends in multi-criteria evaluation of sustainable processes;- Multi-criteria decision making in strategic management based on sustainable criteria.
Keywords: 650; triangular fuzzy neutrosophic sets (TFNSs); MABAC method; MCGDM problems; TFNNs-MABAC method; invested technology enterprise; sub-tour elimination constraint (SEC); asymmetric traveling salesman problem (ATSP); multiple-criteria decision making (MCDM); simultaneous evaluation of criteria and alternatives (SECA); data envelopment analysis (DEA)